2022
DOI: 10.3389/fonc.2022.871132
|View full text |Cite
|
Sign up to set email alerts
|

Would the Addition of Immunotherapy Impact the Prognosis of Patients With Malignant Pericardial Effusion?

Abstract: Pericardial effusion is a common finding in advanced-stage lung cancer. The presence of malignant cells or drainage of exudate effusion in the pericardial space may cause symptoms of dyspnea, pleuritic chest pain, and syncope. In addition to the difficulty physicians face in the detection and diagnosis of malignant pericardial effusion, treatment may be challenging considering the cancer prognosis and cardiovascular stability of the patient. Despite the availability of several treatment modalities for malignan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 44 publications
(45 reference statements)
0
0
0
Order By: Relevance
“…Non-specific findings for pericardial effusions include cardiomegaly on chest radiography and electrical alterations or low-amplitude findings on electrocardiography [ 4 ]. However, echocardiography remains the gold standard for identifying the size, location, and pathophysiologic impact on the heart [ 4 , 12 ]. The treatment pathway depends on the size of the effusion and a patient's clinical presentation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Non-specific findings for pericardial effusions include cardiomegaly on chest radiography and electrical alterations or low-amplitude findings on electrocardiography [ 4 ]. However, echocardiography remains the gold standard for identifying the size, location, and pathophysiologic impact on the heart [ 4 , 12 ]. The treatment pathway depends on the size of the effusion and a patient's clinical presentation.…”
Section: Discussionmentioning
confidence: 99%
“…Although pericardial windows are associated with a lower risk of recurrence, in patients with malignant pericardial effusions secondary to lung carcinoma pericardial windows are associated with a lower overall survival outcome. Previous studies have shown that systemic chemotherapy used independently and in combination with pericardial window or pericardiocentesis are effective [ 12 ]. While balloon pericardiotomy or surgical pericardiectomy are also available options, patients with malignant pericardial effusions tend to undergo pericardial window to prevent re-accumulation [ 5 ].…”
Section: Discussionmentioning
confidence: 99%